The readiness of Iraqi EFL teachers to use mobile learning in teaching English in schools - Ibtihal Hassan Mussa; Nurhasmiza Abu Hasan Sazalli (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The importance of mobile learning (M-learning) has increased during the outbreak of Coronavirus disease 2019 (COVID-19). Level of English foreign language (EFL) teachers to use the technology should be assessed to understand the perception and readiness of EFL teachers to use M-learning. Building on existing literature, this study proposed that performance expectancy, effort expectancy, social influence and facilitating condition will affect positively the readiness to use M-learning. The study also proposed attitude as a mediator and technology self-efficacy as a moderator. The data was collected from 163 EFL teachers in Iraq. The findings showed that facilitating condition, performance expectancy, effort expectancy, and social influence affected positively the readiness to use M-learning. Attitude fully mediated the effect of performance expectancy, effort expectancy, social influence on readiness to use M-learning. Technology self-efficacy did not moderate the effect of the variables but it has a significant direct effect on readiness to use M-learning. Decision makers are recommended to enhance the infrastructure and to initiate training courses to enhance the information technology knowledge of the EFL teachers.